Administrative Accountability in Positive Fictitious State Administrative Decisions and the Protection of Applicants’ Rights in Environmental Licensing - Kartika, Eka Dewi; Laitupa, Salma; Fitriah, Mar’atun; Shalihat Ansar, Nurul (Journal of Law, Politic and Humanities, 2025)
Indonesia’s administrative law system continues to pursue the establishment of an effective, transparent, and accountable governance framework. One of the key issues that has emerged is the application of the Positive Fictitious Administrative Decision (KTUN Fiktif Positif) as regulated in Article 53 paragraph (1) of Law Number 30 of 2014 concerning Government Administration. In the context of environmental licensing, this concept presents new challenges, particularly regarding the accountability of administrative officials for decisions that are deemed legally valid due to inaction or negligence. This research aims to analyze the forms of accountability of administrative officials within the framework of the Positive Fictitious Administrative Decision and to examine the available legal mechanisms to protect applicants’ rights and ensure the effective execution of such decisions. This study employs a normative legal research method with statutory and conceptual approaches. The findings indicate that administrative officials remain liable both administratively and civilly for the issuance of fictitious positive decisions, even when those decisions are legally recognized. Moreover, oversight by the Ombudsman and administrative litigation through the Administrative Court serve as essential instruments to uphold accountability and legal protection for the public. Therefore, judicial reasoning reform and the consistent application of the precautionary principle are necessary to ensure that the acceleration of public services does not compromise environmental protection.